Nurses Working with Unlicensed Assistive Personnel: A Phenomenological Study - Calderon-Margalit, Ronit; Orinovsky, Ira; Toren, Orly (Journal of Clinical and Practical Nursing, 2017)
Objective. To describe the attitudes and behavior of registered nurses in their professional interaction toward unlicensed assistive personnel (UAPs) and to identify areas to develop policy for an effective nursing development and workforce planning. Background: One of the challenges health care systems have been addressing is the integration of the UAPs into the nursing care delivery systems. Study Design: Aphenomenological study involving registered nurses, staff and managerial positions. Data were collected using an in-depth semi-structured interview. Findings: Nurses report an increased task management workload which may lead to a decline in the quality of nursing care. Structural factors that are related to nurses and to UAPs were mentioned as affecting the quality of their professional and collaborative interaction. Conclusions: Training nurses to work with UAPs while developing their communication and managerial skills may improve the quality of care and increase their level of satisfaction.
Keywords: nursing. unlicensed assistive personnel; delegation; attitudes; phenomenological study